2022
DOI: 10.3389/fenvs.2022.940957
|View full text |Cite
|
Sign up to set email alerts
|

Youth’s perception toward ecotourism as a possible model for sustainable use of local tourism resources

Abstract: The knowledge, perception, and behavior of young people toward ecotourism are important for the sustainable development of this sector. The purpose of this research is to evaluate and analyze the knowledge of young Romanian students about ecotourism and the main ecotourism destinations in Romania, their behavior in relation to the practice of this form of sustainable tourism at the local level in the last 2 years (2020 and 2021), and people’s use of the Internet for planning holidays and digital applications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The nature of the study was a survey and gathered data with the help of adapted constructs. Such as social inequality with a 6-item scale and economic inequality 6-items by (Ap & Crompton, 1998), support for tourism 8-items scale by Munanura et al (2021), tourism resources 5-item scale was adapted from the study of Stanciu et al (2022). The questionnaire scale was a 5-point Likert scale and control the demographic variable with quasi-experimental survey-based research statistics.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the study was a survey and gathered data with the help of adapted constructs. Such as social inequality with a 6-item scale and economic inequality 6-items by (Ap & Crompton, 1998), support for tourism 8-items scale by Munanura et al (2021), tourism resources 5-item scale was adapted from the study of Stanciu et al (2022). The questionnaire scale was a 5-point Likert scale and control the demographic variable with quasi-experimental survey-based research statistics.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of ecotourism [32] and agritourism [33,34] in communities bordering protected areas can be a model of sustainable use [34] of the tourism resources that the area offers [35,36]. Increased investment in building a smart rural tourism environment leads to improved living conditions for locals and tourists and facilitates access to good-quality public services [37], while providing ecosystem services [38].…”
Section: Smart Tourist Villagesmentioning
confidence: 99%
“…For example, Castilho et al (2021) studied the overall ecological efficiency of 22 Latin American and Caribbean countries and found that the arrival of tourists reduces the ecological efficiency of these countries [45]. Based on the background of green development, the co-integration relationship between regional tourism income and economic and ecological effects was analysed, and the spatiotemporal evolutionary trajectory of tourism eco-efficiency and tourism economy was explored to analyse the interactive response relationship between tourism eco-efficiency and tourism economic development [46][47][48][49][50].…”
Section: Literature Reviewmentioning
confidence: 99%